Risk factors for prolonged length of stay in patients undergoing surgery for intramedullary spinal cord tumors. (September 2021) - Waguia, Romaric; Wang, Timothy Y.; Mehta, Vikram A.; Ramirez, Luis; McCray, Edwin; Pennington, Zach; Price, Meghan; Dalton, Tara; Baëta, César; Sciubba, Daniel M.; Karikari, Isaac O.; Abd-El-Barr, Muhammad M.; et al.
Highlights: Dependent neuro-functional status predicts prolonged length of stay in IMSCT. Severe ASA-class predicts prolonged length of stay in IMSCT. Transfer to tertiary medical center predicts prolonged length of stay in IMSCT. 10% of patients undergoing surgery for IMSCT are readmitted within 30-days. Reoperation rate of those readmitted is 34.0% Abstract: Primary spine tumors are rare neoplasms that affect about 0.62 per 100, 000 individuals in the US. Intramedullary spinal cord tumors (IMSCTs) are the rarest of all primary tumors involving the spine and can cause pain, imbalance, urinary dysfunction and neurological deficits. These types of tumors oftentimes necessitate surgical treatment, yet there is a lack of data on hospital length of stay and complication rates following treatment. Given that treatment candidacy, quality of life, and outcomes are tied so closely to potential for prolonged length of stay and postoperative complications, it is important to better understand the factors that increase the risk of these outcomes in patients with IMSCTs. Methods: The National Surgical Quality Improvement Program (NSQIP) database was queried for all patients undergoing surgery for treatment of intramedullary spinal cord tumors between 2005 and 2017. Univariate and multivariate analysis were performed to assess patient risk factors influencing prolonged length of stay and post-op complications. Results: A total of 638 patients were included in the analysis. Pre-operative American Society of Anesthesiology (ASA) physical status classification of 3 and above (OR 1.89; p = 0.0005), dependent functional status (OR 2.76; p = 0.0035) and transfer from facilities other than home (OR 8.12; p <0.0001) were independent predictors of prolonged length of stay (>5 days). The most commonly reported complications were pneumonia (5.7%), urinary tract infection (9.4%), septic shock (3.8%), superficial incisional infection (5.7%), organ or space infection (5.7%), pulmonary embolism (11.3%), DVT requiring therapy (15.1%) and wound dehiscence (5.7%). Conclusion: Our study demonstrated the significant influence of clinical variables on prolonged hospitalization of IMSCT patients. This should be factored into clinical and surgical decision making and when counseling patients of their expected outcomes.